Absence of an especially toxic clone among isolates of Actinobacillus actinomycetemcomitans recovered from army recruits - Macheleidt, Alexander; Müller, Hans-Peter; Eger, T.; Putzker, M.; Fuhrmann, A.; Zöller, L. (Clinical oral investigations, 1999)
Actinobacillus actinomycetemcomitans is a major periodontal pathogen which is associated with early-onset and adult periodontitis. The organism has been shown to be widely distributed among dentate, healthy individuals as well. It has been demonstrated that A. actinomycetemcomitans shows great genetic diversity. An especially virulent clone of the organism (JP2-like) with a specific 530-base pair (bp) deletion in the promoter region of the leukotoxin gene has been isolated from localized juvenile periodontitis patients and related subjects of African and African-American origin. The aim of the present study was to examine the presence of this specific clone employing specific oligonucleotide primers in a polymerase chain reaction among 51 isolates of A. actinomycetemcomitans recovered from 201, 18- to 25-year-old recruits with no or minor periodontal disease. In addition, clinical isolates from 37 periodontitis patients were analyzed as well as reference strains ATCC 29524, NCTC 9710, Y4 and JP2. Primers amplifying a specific 285-bp amplification product in the ltxA region of the leukotoxin gene and a specific 547-bp amplification product of 16 S rRNA were used to genetically confirm identification of the organisms. Primers amplifying sequences in the leukotoxin promoter region were used to identify the deletion. Species specific primers definitively identified all A. actinomycetemcomitans isolates. No isolates from army recruits or the reference strains displayed the deletion in the leukotoxin promoter region. However, in the periodontitis group, a 24-year-old individual from Ghana with localized juvenile periodontitis was identified with an intraoral infection with highly toxic A. actinomycetemcomitans (JP2-like). Present results confirm previous observations of absence of a highly toxic clone of A. actinomycetemcomitans among periodontally healthy and diseased Caucasians as well as a possible presence in localized juvenile periodontitis in individuals of African origin.
Gesehen am 16.02.2021